NEURODYNAMIC AND PREDICTABILITY OF ALPHA-STIMULATING BIOFEEDBACK COURSE IN SPORTSMEN AND PERSONS OCCUPYING PHYSICAL CULTURE - L. P. Cherapkina; V. G. Tristan; S. P. Styopochkina (Бюллетень сибирской медицины, 2013)
The 15-days neurofeedback course was conducted with the purpose of neurodynamic and predictability assessment of mastering of arbitrary regulation skill of electroencephalographic (EEG) spectral power in alpha-band in sportsmen (n=260) and persons (n=69) occupying physical culture. The electroencephalographic parameters being predictors of neurofeedback course were defined in result of research. It was showed that different neurodynamical changes in examined groups supported training successfulness.